MUI FATWA NO. 2/2025 ON EQUITABLE TAXATION: A MAQASID SYSTEMS AND NKRI-CONTEXTUAL ANALYSIS - Ryan Bianda; Nur Hasan; Muhammad Yosef Niteh; Maad Ahmad (JURNAL HAKAM, 2026)
This article examines MUI Fatwa No. 2/2025 on equitable taxation as a religious-normative framework for evaluating fiscal legitimacy in Indonesia. The study addresses the question of how taxation, as a civic obligation, can be justified within Islamic legal reasoning in relation to justice, public welfare, zakat, and state accountability. Using a qualitative, normative, textual method, the article treats the fatwa as the primary source and analyzes it through Jasser Auda’s MAQASID systems approach and KH. Afifuddin Muhajir’s NKRI contextual understanding of the state as a wasīlah for realizing public welfare. The findings reveal that the fatwa does not consider taxation to be inherently legitimate simply because it is imposed by the state. Rather, the fatwa establishes equitable taxation through three main categories: conditional legitimacy, distributive protection, and procedural integrity. Taxation is legitimate only when public resources are insufficient, fiscal burdens are imposed on those who can pay, essential needs are protected from excessive taxation, and tax revenue is managed with amānah (trustworthiness), transparency, accountability, professionalism, and fairness. The fatwa also considers zakat a tax-reducing factor, addressing the risk of overlapping fiscal burdens for Muslim taxpayers. The article argues that the fatwa does not replace the state’s legal-fiscal authority but rather provides an ethical benchmark for assessing whether taxation is just, accountable, and oriented toward public welfare under NKRI conditions.